Образ женщины в творчестве Владимира Войновича - Zywert, Aleksandra (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
This article is devoted to the issue of the evolution of how a woman is portrayed in Vladimir Voinovich’s works. In the author’s early works a woman’s portrayal was relatively poor, stereotypical and neutral; then it became more diverse and profound from the point of view of its ideological significance. A woman steps away from the man’s background and transforms herself into his equal partner in the process of creating reality.
A woman’s portrayal in Vladimir Voinovich’s works
Portret kobiety w twórczości Władimira Wojnowicza